2019
DOI: 10.1016/j.tet.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Flavin-dependent biocatalysts in synthesis

Abstract: The diverse chemistry possible with flavin cofactors positions flavin-dependent enzymes as versatile synthetic tools. This focused review highlights applications of flavin-dependent enzymes in organic synthesis. Select examples of monoamine oxidases, ene-reductases, monooxygenases and halogenases in target-oriented synthesis are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
(61 reference statements)
0
34
0
Order By: Relevance
“…As flavin-dependent monooxygenases are attractive for many applications ( 3 , 10 , 11 , 12 , 14 , 54 ), identification of residues important for catalysis provides basic knowledge for future rational design in enzyme engineering. As HadA is useful for many applications including detoxification and biodetection ( 9 ), the structural basis reported here should be useful for improving HadA for industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…As flavin-dependent monooxygenases are attractive for many applications ( 3 , 10 , 11 , 12 , 14 , 54 ), identification of residues important for catalysis provides basic knowledge for future rational design in enzyme engineering. As HadA is useful for many applications including detoxification and biodetection ( 9 ), the structural basis reported here should be useful for improving HadA for industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by the identification of such highly effective guanidino-flavins for bacterial inactivation, we were interested to see if the trend would be similar for coronaviruses, specifically, the SARS-CoV-2 surrogate, murine hepatitis virus A59 strain (MHV-A59). 4 > It has already been demonstrated that riboflavin can effectively inactivate both enveloped and non-enveloped viruses in blood products using UV light, [20][21][22][23][24] but much lower efficacy was observed using visible light (0.4x10 5 lx, 0.5-2 h) against hepatitis B virus (HBV). 77,78 In order to evaluate possible applicability towards topical infection treatment and pathogen-inactivating surface coatings or textiles, [79][80][81][82] we used an in vitro S3 for 17Cl-1 cytotoxicity data).…”
Section: Photodynamic Inactivation Of Murine Hepatitis Virus (Mhv-a59)mentioning
confidence: 99%
“…1,2 Due to their rich redox chemistry and ability to mediate a wide range of both oxidative and reductive organic transformations, flavin-containing enzymes are prominently used as biocatalysts. 3,4 Flavins are also involved in the regulation of photochemical pathways due to strong blue light absorption, which results in the generation of highly oxidising excited states that can elicit biological signalling events or responses. [5][6][7][8] This photoexcitation process has been exploited in a number of photocatalytic applications, whereby modification of the flavin chromophore can enable the formation of high potential oxidative and reductive intermediates to afford useful synthetic methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Using the example of oxyfunctionalisation enzymes such as cytochrome P450 monooxygenases (P450s), [51,52] unspecific peroxygenases (UPOs), [53,54] flavin‐dependent monooxygenases, [55,56] Rieske dioxygenases, [57,58] and αKGDs, [59,60] this perspective complements recent cutting‐edge biocatalysis review articles [2,14,16,17,61,62] in order to aid the transition towards sustainable chemistry by wide‐spread combinations of chemo‐ and biocatalysis [63–66] . Many of the here presented examples do not involve commercial enzyme kits yet, but rather self‐generated mutant libraries.…”
Section: Introductionmentioning
confidence: 96%